Synthesis of 1, 5‐Pentanediol by Hydrogenolysis of Furfuryl Alcohol over Ni–Y2O3 Composite Catalyst. Issue 14 (14th June 2017) - Wijaya, Husni Wahyu; Kojima, Takashi; Hara, Takayoshi; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract: The addition of Y2 O3 into Ni formed a composite catalyst that selectively produced 1, 5‐pentanediol rather than 1, 2‐pentanediol in the hydrogenolysis of furfuryl alcohol at 2.0 MPa H2 and 423 K. Clearly, 1, 5‐pentanediol was produced over the Ni 0 –Y2 O3 boundary. This report highlights the properties of Ni–Y2 O3, catalytic performance, and reaction route in the synthesis of 1, 5‐pentanediol from furfuryl alcohol. Abstract : Two steps, together : A Ni–Y2 O3 composite catalyst is employed to produce 1, 5‐pentanediol in the hydrogenolysis of furfuryl alcohol with high selectivity. The Ni 0 –Y2 O3 boundary is clearly active and selective in the C−O bond hydrogenolysis.